A Bipolar-Bisection Piecewise Encoding Scheme for Multi-Source Reverse Time Migration (Communications in Computational Physics, 2020)
Conventional shot-record reverse time migration (RTM) suffers from a highcomputational burden when dealing with massive data. The computational cost ofRTM can be reduced by shot-encoding techniques, and plane-wave encoding is a commonly used and effective shot-encoding scheme. However, plane-wave encoding requires long time padding to avoid information loss, which decreases the efficiencyof the time-domain wavefield extrapolator, and the time padding becomes longer withthe increasing distance between multiple sources. The piecewise plane-wave encodingscheme cuts multiple sources into several segments prior to implementing plane-waveencoding, hence reduces the time padding, but brings new crosstalk due to the mutualinterference between shots in different source segments. We suppress the crosstalkartifacts by a new bipolar-bisection amplitude encoding method, in which half of theencoding array of each migration is different from that of any other migrations to reduce the number of crosstalk terms with as few migrations as possible. We embed thebipolar-bisection method into piecewise plane-wave encoding. Compared with plane-wave encoding, the proposed scheme requires considerably shorter time padding andthus works more efficiently and can generate a qualified imaging result. The feasibilityof the proposed method is tested on the 2D SEG/EAGE salt model and the Marmousimodel.